2004
DOI: 10.1381/096089204323013488
|View full text |Cite
|
Sign up to set email alerts
|

Post-anesthesia Recovery after Infusion of Propofol with Remifentanil or Alfentanil or Fentanyl in Morbidly Obese Patients

Abstract: In morbidly obese individuals, alfentanil or fentanyl and remifentanil can be safely used, but there is a higher rate of PONV and postoperative pain in the remifentanil group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 7 publications
1
20
1
2
Order By: Relevance
“…In the fentanyl group, anesthesia was induced with fentanyl (0.5 lg/kg), lidocaine (100 mg), thiopental (1-4 mg/kg), and succinylcholine (0.6 mg/kg). Anesthesia was maintained with fentanyl infusion (0.5 lg d kg À1 d h À1 ), consistent with previous dosing [19]. End-tidal desflurane concentration was adjusted to maintain the BIS at 45 to 50 during surgery.…”
Section: Methodsmentioning
confidence: 99%
“…In the fentanyl group, anesthesia was induced with fentanyl (0.5 lg/kg), lidocaine (100 mg), thiopental (1-4 mg/kg), and succinylcholine (0.6 mg/kg). Anesthesia was maintained with fentanyl infusion (0.5 lg d kg À1 d h À1 ), consistent with previous dosing [19]. End-tidal desflurane concentration was adjusted to maintain the BIS at 45 to 50 during surgery.…”
Section: Methodsmentioning
confidence: 99%
“…This difference appears to be smaller in patients with a high postoperative analgesics requirement [11,62,73,94], and larger in patients with low postoperative analgesic requirement [10,25,39,51,57,61,88]. Most of the latter studies [10,25,57,61,88] involved minor surgical procedures that were less likely to cause severe postoperative pain.…”
Section: ó 2007 the Authorsmentioning
confidence: 97%
“…NIMV has also been successfully used in selected patients suffering acute hypoxemic respiratory failure. 21 Although both masks performed similarly with regard to improving vital signs and gas exchange and avoiding intubation, the nasal mask was less well tolerated than the oronasal mask in patients with acute respiratory failure. 22 A meta-analysis by Ferreyra et al suggested that CPAP decreased the postoperative pulmonary complications, and recommended its use in the treatment of post-abdominal-surgery respiratory complications.…”
Section: Group C (N=20)mentioning
confidence: 92%